PROSPECTS FOR THE PURIFICATION OF SURFACE RESERVOIRS FROM BIOGENIC ELEMENTS - Tekebayeva, Zh.B.; Bazarkhankyzy, A.; Temirbekova, A.Zh.; Bissenova, G.N.; Kulagin, A.A.; Tynybayeva, I.K.; Temirkhanov, A.Zh.; Askarova, N.B.; Sarmurzina, Z.S. (Eurasian Journal of Applied Biotechnology, 2022)
The threat of water scarcity and inefficient management of water resources can become a major obstacle to the sustainable economic growth and social development in Kazakhstan. Pollutants enter surface water bodies mainly as a result of human activities. Among the various substances present in wastewater, nitrogen and phosphorus compounds deserve the most attention. Getting into water bodies, they cause eutrophication, which can be dangerous for the ecosystem as a whole and for humans. Among the various methods of wastewater treatment, biological methods are considered the most promising and effective. In this regard, the search for active microorganisms and microalgae for the purification of water bodies from biogenic elements is especially relevant. The object of the study was Lake Big Taldykol, recreated asa result of the reclamation of theTaldykol wastewater evaporator and being one of the important water bodies of the city of Nur-Sultan. It has been revealed that in recent years the main substances polluting the water bodies of the capital are total phosphorus, calcium, magnesium, chlorides, sulfates, total iron, mineralization and chemical oxygen demand (COD). Chemical analysis of water samples from Lake Big Taldykol showed excesses in chlorides, sulfates, COD, total iron, suspended solids, and dry residue. The prospects for the use of microorganisms that are destructors of biogenic and organo-mineral pollutants are considered. Cultures of microorganisms and green microalgae were isolated from the water of Big Taldykol Lake. The use of the studied microorganisms can reduce the amount of biogenic elements, thereby reducing their potential for eutrophication.